2023
DOI: 10.3390/cancers15194726
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Perceived Relationship between Sun Exposure and Melanoma in Atlantic Canada: A Consensual Qualitative Study Highlighting a “Sunscreen Paradox”

Sauliha Alli,
Jonathan LeBeau,
Agustina Hasbani
et al.

Abstract: Globally, cutaneous melanoma (CM) incidence is increasing, with sun exposure identified as a key modifiable risk factor. The Atlantic provinces of Canada display varied CM incidence rates: New Brunswick aligns with the national average, while Nova Scotia and Prince Edward Island exceed it, and Newfoundland and Labrador fall below this benchmark. We investigated the relationship between sun exposure and CM in these provinces. Twenty-two focus groups encompassing 95 Atlantic Canada residents were conducted and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This has already been proven by multiple studies that found that individuals with a lower perceived UV sensitivity, as characterised by the Fitzpatrick skin types, were more likely to incorporate sunscreen usage when exposed to the sun [ 24 , 25 ]. This could be due to a false sense of security or a “sunscreen paradox” rooted in misconception about the amount of melanin in one’s skin and the subsequent protection it offers against UVA and UVB rays [ 26 , 27 , 28 , 29 ]. Furthermore, the Fitzpatrick classification for skin types has a poor correlation with UV sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has already been proven by multiple studies that found that individuals with a lower perceived UV sensitivity, as characterised by the Fitzpatrick skin types, were more likely to incorporate sunscreen usage when exposed to the sun [ 24 , 25 ]. This could be due to a false sense of security or a “sunscreen paradox” rooted in misconception about the amount of melanin in one’s skin and the subsequent protection it offers against UVA and UVB rays [ 26 , 27 , 28 , 29 ]. Furthermore, the Fitzpatrick classification for skin types has a poor correlation with UV sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from those with skin type 1, those with darker skin types were less likely to adopt safer behaviours in the sun. This could be due to a false sense of security that darker skin helps to protect against UVA and UVB rays and, thus, could hamper individuals from changing their behaviour [ 26 , 27 , 28 , 29 ]. However, this trend was reversed when looking at protective headwear use, with the tendency to adopt this behaviour decreasing with darker skin types.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the duration of sun exposure, especially unprotected sun exposure, may be a confounding variable in these studies that have found sunscreen use to be associated with higher melanoma rates. Further, many of these studies included sunscreens with a sun protection factor (SPF) lower than 30; however, 30 is the minimum SPF recommended by the American Academy of Dermatology for daily use [42], so this SPF or higher should be used in studies. Even when sunscreen with an adequate SPF is used, it is also well established that sunscreen users typically apply just a fifth to a third of the amount of sunscreen required to achieve the maximum SPF potential [35].…”
Section: Discussionmentioning
confidence: 99%